Identification and functional analysis of α-farnesene synthase gene from the cabbage Brassica oleracea - ZHANG Tong; WANG Yiping; GE Yang; NTIRI Eric; ZHOU Wenwu (浙江大学学报. 农业与生命科学版)
In order to illuminate the biological function of α-farnesene synthase gene (BoTPSa) from the cabbage Brassica oleracea, the BoTPSa gene was cloned and its expression levels were measured in the plants treated by different environmental stresses. Then the protein was heterologously expressed in Escherichia coli prokaryotic expression system and its biochemical function was determined, and the subcellular localization of this protein was studied in Arabidopsis thaliana. The results showed that BoTPSa gene and its homologous genes from cruciferous plants (especially from Brassica) were quite similar in the nucleic acid sequence level, indicating that this gene had conserved structures. The stresses including the damages caused by diamond back moth (DBM), aphids, the high and low temperatures could significantly affect the expression levels of BoTPSa, and DBM damage caused the highest change of gene expression level among all the tested stresses, indicating that this gene was involved in the insect herbivore and abiotic stresses responses in cabbage. The BoTPSa protein was not localized in chloroplasts or cell nucleus, and could catalyze the formation of several terpenoids in vitro, which was a multifunctional enzyme. Above all, this study systemically characterizes the α-farnesene synthase gene (BoTPSa) from the cabbage, which could provide a basis for the functional and applied studies of terpene synthase in cruciferous plants.